Alzheimer's disease pathology is associated with earlier alterations to blood–brain barrier water permeability compared with healthy ageing in TgF344‐AD rats. (15th March 2021) - Dickie, Ben R.; Boutin, Hervé; Parker, Geoff J. M.; Parkes, Laura M.
Abstract : The effects of Alzheimer's disease (AD) and ageing on blood–brain barrier (BBB) breakdown are investigated in TgF344‐AD and wild‐type rats aged 13, 18 and 21 months. Permeability surface area products of the BBB to water ( PS w ) and gadolinium‐based contrast agent ( PS g ) were measured in grey matter using multiflip angle multiecho dynamic contrast‐enhanced MRI. At 13 months of age, there was no significant difference in PS w between TgF344‐AD and wild‐types ( p = 0.82). Between 13 and 18 months, PS w increased in TgF344‐AD rats ( p = 0.027), but not in wild‐types ( p = 0.99), leading to significantly higher PS w in TgF344‐AD rats at 18 months, as previously reported ( p = 0.012). Between 18 and 21 months, PS w values increased in wild‐types ( p = 0.050), but not in TgF344‐AD rats ( p = 0.50). These results indicate that BBB water permeability is affected by both AD pathology and ageing, but that changes occur earlier in the presence of AD pathology. There were no significant genotype or ageing effects on PS g ( p > 0.05). In conclusion, we detected increases in BBB water permeability with age in TgF344‐AD and wild‐type rats, and found that changes occurred at an earlier age in rats with AD pathology. Abstract : In this study we use multi‐flip angle multiecho dynamic contrast‐enhanced MRI to measure BBB surface area products of gadolinium contrast agent ( PS g ) and water ( PS w ) in TgF344‐AD rats and wild‐types at multiple time points to assess ageing effects. We observe significant increases in PS w with age in both TgF344‐AD and wild‐type rats but found changes occurred earlier in TgF344‐AD rats. No alterations in PS g were observed with age or genotype.